Real-Time Management — An Analogy - Borovits, Israel; Segev, Eli (Academy of Management Review, 1977)
In this article the authors examine the time-scheduling policy of real-time management based on an analogy between real-time management and a scheduling policy of data processing systems. They note that existing scheduling policies have increased the productivity of data processing by improving the scheduling of tasks as well as the allocation of resources. They suggest that similar policy changes could improve real-time management. They define real-time management as managerial jobs that are associated with the present tasks involved in an organization such as the handling of daily involuntary disturbances. They note that because of these variables it can be difficult to improve the productivity of real-time management; however, improved scheduling may offer some solutions.